Association between major socio-demographic and psychosocial factors with the dietary pattern among elderly people in Amman, Jordan - O. IBRAHIM, Mohammed (Nutrición Clínica y Dietética Hospitalaria, 2021)
ABSTRACT Introduction: The population of elderly people has increased significantly in recent decades. Their health is partially influenced by the nature of dietary pattern they choose. This study was designed to identify the association of major psychosocial and socio-demographic factors with the dietary pattern among elderly people in Amman, Jordan. Methods: Cross-sectional studies of 116 elderly Jordanian participants were enrolled in the study. The data about participants were collected using socio-demographic questionnaire, MEDFICTS dietary assessment questionnaire, perceived stress scale (PSS), centers for epidemiological studies depression scale (CES-D), and multidimensional scale of perceived social support (MSPSS). Statistical analysis was conducted using SPSS (version 23), with statistical significance set at p-value <0.05. Results: The average total score of MEDFICTS questionnaire was 55.79 ± 8.82. The attitude of participants was more concentrated on snacks, table fat, convenience foods, in baked goods, and frying foods. About 44.8% of participant scored ≥ 70 in the MEDFICTS questionnaire. Consumption of unhealthy dietary pattern has positive significant associations among females (β=0.59, p =0.001) and participants with lower monthly income (β=0.39, p= 0.003). Higher scores of depressive symptoms and perceived stress were found to be significantly higher for those participants who scored ≥ 70 in the MEDFICTS questionnaire and vice versa regarding social support. Conclusion: The socio-demographic and psychosocial factors in this study play crucial role in determining the tendencies toward unhealthy food patterns among elderly people. It is highly recommended to investigate the role of other factors through longitudinal studies among elderly people.